ОСВІТНІ ІННОВАЦІЇ У ПІДГОТОВЦІ ПРАКТИЧНОГО ПСИХОЛОГА НА КОМПЕТЕНТНІСНІЙ ОСНОВІ - Лозова, Ольга (ОСВІТОЛОГІЯ, 2016)
У статті розглянуто динаміку змін вищої освіти психологів у США. В контексті перспективи членства України в Євросоюзі обгрунтовано необхідність оновлення змісту фахової підготовки практичних психологів. Представлено досвід стратегічної розробки і тактичної реалізації вимог Європейського стандарту (EuroPsy) та Проекту «Гармонізація освітніх структур в Європі» в освітніх програмах підготовки практичого психолога Київського університету імені Бориса Грінченка. Описано програмові інновації, що покликані забезпечити високу кваліфікацію та конкурентоспроможність випускників на ринку праці. The experience of strategic development and implementation of requirements of the European standard (EuroPsy) and the «Harmonisation of European Educational Structures» project in educational programs of Borys Grinchenko Kyiv University is presented. The upgrade of educational programs is described in the context of unification with European standards for future psychologists training. The competences of practical psychologists were made consistent with EuroPsy mode regarding (a) functions of psychologist and (b) competencies psychologist. Meanwhile, general competences of psychologists were made consistent with the Tuning project (c), professional and cognitive (d) and professional practice (e) competences were developed by the Applied Psychology Department of Borys Grinchenko Kyiv University. All competences of psychologists (a total of 14) were divided into basic (6) and auxiliary (8) groups. Programmatic innovations designed to provide qualifications and competitiveness to bachelors and masters were described. Programs consist of modules which include: compulsory subjects aimed at creating general and professional competences, optional subjects, different practices and the final student examination.